Analysis of the influence of parenteral cancer chemotherapy on the health condition of oral mucosa - Rahnama, Mansur; Madej-Czerwonka, Barbara; Jastrzębska-Jamrogiewicz, Izabela; Jamrogiewicz, Rafał (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : The present study was aimed at estimating the prevalence of oral complications in cancer patients receiving chemotherapy. Material and methods : The study was conducted on a group of 58 patients treated with chemotherapy (study group). The control group consisted of 30 healthy patients. Dental status and oral mucosa were examined using the criteria of the National Cancer Institute Toxicity Criteria Scale. The levels of stimulated and unstimulated saliva flow were analysed. Results : In the group of patients treated with chemotherapy, 59% of patients had inflammatory changes of the soft tissues of the mouth, such as erythema, erosions, or ulcers, which were discovered during dental examination. Such changes occurred in only 10% of patients in the control group. Six of the patients treated with chemotherapy reported pain with intensity was so severe that it caused swallowing difficulties. Patients in the study group frequently complained about the presence of dry mouth, taste disturbances, nausea, and vomiting. These symptoms occurred in 70% of patients undergoing oncological treatment. In both stimulated and unstimulated saliva secretion, the rates were significantly lower in patients from the research group, when compared to the control group.